Workshop Perawatan Lansia Pada Kader Surabaya Hebat di RW 13 Kelurahan Kebraon Kecamatan Karangpilang Surabaya - Djajanti, Cicilia Wahyu; Dwianto, Ignatius Heri; Ekawati, Nora (Jurnal Abdimas Kesehatan (JAK), 2025)
The elderly face complex problems due to physical, psychological, social, and emotional changes that require comprehensive support to help them adapt. The majority of diseases experienced by the elderly today are degenerative diseases such as diabetes mellitus (DM) and hypertension, which require lifelong support.Problems Faced by the Elderly in Posyandu Lansia Sehat Bahagia RW 13 Kebraon Indah Permai, Kelurahan Kebraon, Kecamatan Karang Pilang, Surabaya.Out of 125 elderly individuals, 45 who attended the Posyandu were diagnosed with hypertension. However, they were found to be irregular in taking their medication and had incorrect medication-taking practices, despite frequent education from healthcare professionals and cadres. Role of Health Cadres. Health cadres are volunteers recruited from and by the community to assist in health services. Their presence is closely linked to routine services at Posyandu. Community Service Activities.STIKES Katolik St Vincentius A Paulo Surabaya conducted community service activities at Posyandu Lansia Sehat Bahagia, providing education and workshops to Surabaya Hebat cadres on supporting elderly care for those with hypertension. The workshop included training on blood pressure measurement, aiming to optimize elderly care at home through the enhanced capabilities of health cadres.